PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP ALOKASI BELANJA DAERAH PADA PEMERINTAH KABUPATEN/KOTA PROVINSI JAWA TIMUR - Dwi Setyowati (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2014)
This study aims to determine the effect of local revenues and general allocation funds to the regional expenditure of East Java Province Year 2007 up to Year 2008. Methods conducted in this study is a quantitative research method using classical assumption data analysis techniques, multiple linear regression and hypothesis testing which is processed in SPSS (Statistical Package for the Social Science) for windows version 16.0. The results of the analysis show that the Original Revenue and DAU have a significant influence on the Regional Expenditure Allocation. If further seen, the level of dependence of local expenditure allocation is more dominant to the Regional Original Income than DAU. Based on t test with calculation of SPSS for windows version 16.0 can be concluded that among variable of original revenue of area and general allocation fund which have the most dominant influence to allocation of regional expenditure of East Java Province is variable of original income of region. Because the value of t arithmetical variable of original revenue area is bigger than t count the variable of general allocation fund that is 2,845> 1,332 hence Ho decision is rejected, it means that local revenue has the most dominant influence to the allocation of regional expenditure in East Java Province.